NILAI ESTETIKA DALAM TARI LENGGER PUNJEN DI DUSUN GIYANTI DESA KADIPATEN KECAMATAN SELOMERTO KABUPATEN WONOSOBO - Haki Wanudya Taranggana (TANDIK : Jurnal Seni dan Pendidikan Seni, 2021)
This study aims to describe the aesthetic value contained in the Lengger Punjen Dance in Giyanti, Kadipaten, Selomerto, Wonosobo. The description is done by observing the form of presentation related to the elements of choreography in dance. Research method by descriptive qualitative study carried out in mid-February to April 2020. The object of this research is the Lengger Punjen Dance in Giyanti, Kadipaten, Selomerto, Wonosobo, while the research subjects are art activists, maestro lengger, Lengger Punjen dancers and artists who are also grandchildren of the creators of the Lengger Punjen Dance. Data collected by observation, in-depth interviews, and documentation studies. From the data that has been analyzed, conclusions are drawn. In order to obtain valid data, a data validity test was performed by used the source triangulation method. The results of this study are: 1. Lengger Punjen Dance is a dance created to create a new nuance in lengger art and has a function as entertainment, performing arts and ceremonies. 2. The aesthetic value of the Lengger Punjen Dance can be seen from the aesthetic elements which consist of: a form seen in its shape and structure, which is describing family and death and its structure consists of a unified whole and consists of a pure motion structure and meaningful motion, the weight shown in the atmosphere wisdom, ideas inspired by the Bondhan Kendi Dance form and the messages contained namely the message of advice and religious messages, the appearance is shown in the talents and skills that must be routinely trained and the means to support the appearance. 3. The aesthetic value of the Lengger Punjen Dance can be seen from the aesthetic variety which consists of: harmony can be shown through fashion, movement, and property, balance can be shown through motion when punjen (raised on the shoulder), complexity is shown through the attraction of lifting a female dancer (munji) and contrast can be seen very strikingly from the development of hand movements if danced by several pairs of dancers because there is no visible harmony between the dancers.